Upaya Pembentukan Perilaku Peduli Lingkungan Hidup dan Kesehatan Lingkungan Sekolah Kepada Siswa Menuju Sekolah Adiwiyata Di SDN 211/IV Kota Jambi - Fajrina Hidayati; Fitria Eka Putri; Andy Amir (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2022)
Various forms of environmental education in schools, namely, environmentally cultured schools, green schools, and healthy schools. The term adopted by the government is Adiwiyata. SDN 211/IV Jambi is located not far from the city center and has a beautiful environment, this school has a fairly conducive land to support the Adiwiyata program and has teachers who love and care about the environment. The purpose of this dedication is so that future Adiwiyata activities will be realized and be successful and sustainable. This service activity is supported by the principal and teachers. With this service activity, it is hoped that students as future leaders will be equipped and able to implement environmentally sound development and not only pursue economic and social benefits. Based on the results of community service activities carried out, it was found that there were no specific policies regarding the environment that could be applied in schools. In addition, the environmental curriculum is still integrated with several subjects and has not involved other parties in environmental conservation activities. There is an increase in knowledge after education about adiwiyata, especially environmental care and waste management in schools. It is hoped that schools will be able to maintain existing educational facilities and improve them and begin to develop adiwiyata school policies and cooperate with the Environment Agency so that these activities can be successful.Keywords: Adiwiyata, Caring for the environment, Waste management